Back on Blossom Street - Macomber, Debbie (Macomber, Debbie. Blossom Street novel ;, 2007)
When Susannah, the owner of a new flower store, and her employee, a young widow named Colette Blake, join the knitting class at A Good Yarn, they meet a group of unforgettable women who offer them life-changing advice, support, and friendship.